2019
DOI: 10.1002/lno.11134
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater inflows control patterns and sources of greenhouse gas emissions from streams

Abstract: Headwater streams can be important sources of carbon dioxide (CO 2 ) and methane (CH 4 ) to the atmosphere. However, the influence of groundwater-stream connectivity on the patterns and sources of carbon (C) gas evasion is still poorly understood. We explored these connections in the boreal landscape through a detailed study of a 1.4 km lake outlet stream that is hydrologically fed by multiple topographically driven groundwater input zones. We measured stream and groundwater dissolved organic C (DOC), CO 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(122 citation statements)
references
References 51 publications
12
101
1
Order By: Relevance
“…litterfall or DOC; Demars, ; Roberts, Mulholland, & Hill, ). In our study, ER was strongly related to discharge (Figure S10), which has been reported elsewhere for other small northern streams (Demars, ; Lupon et al, ). These authors suggest that discharge could regulate the activity of stream heterotrophs through the delivery of terrestrial organic C. Consistent with this supply mechanism, previous work in the Miellajokka catchment has shown that DOC increases with discharge (Giesler et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…litterfall or DOC; Demars, ; Roberts, Mulholland, & Hill, ). In our study, ER was strongly related to discharge (Figure S10), which has been reported elsewhere for other small northern streams (Demars, ; Lupon et al, ). These authors suggest that discharge could regulate the activity of stream heterotrophs through the delivery of terrestrial organic C. Consistent with this supply mechanism, previous work in the Miellajokka catchment has shown that DOC increases with discharge (Giesler et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that these streams mineralize substantial amounts of the organic C received from land that otherwise would have been exported downstream to lakes or marine systems. Our reported values of the contribution of aquatic NEP to CO 2 evasion are high compared to other studies of small streams in high latitudes (40%-75%; Lupon et al, 2019;Rasilo et al, 2016), and typically the largest contributions to date have been observed for considerably larger rivers (85%-97%; e.g. Cole & Caraco, 2001;Lynch, Beatty, Seidel, Jungst, & DeGrandpre, 2010).…”
Section: Contribution Of Stream Nep To Co 2 Evasioncontrasting
confidence: 57%
“…In fact, groundwater has been shown to be important for the CO 2 dynamics in the streams in the Vallon de Nant catchment (RIC, AND, ANU) (Horgby et al 2019). Beyond our mountain streams, groundwater is now being increasingly recognized to drive CO 2 concentration and fluxes in various headwater streams (Duvert et al 2018, Lupon et al 2019. Because of the inherent link between gas exchange velocity and discharge, we found positive responses in k CO2 to q (100%, P<0.05) and F CO2 to increasing q , respectively (53%, P<0.05) ( Table S2).…”
Section: Annual Responsiveness Of Co 2 Concentration and Evasion Fluxmentioning
confidence: 99%
“…This would also explain why the influence of VSAs on DOC in streams is temporally variable (Lupon et al. ) and the incongruencies among studies. Lupon et al.…”
Section: Discussionmentioning
confidence: 99%